PTH-169 Global inverse associations between gastric and oesophageal adenocarcinoma supports h. pylori infection protecting from latter. (22nd June 2015) - Derakhshan, MH; Arnold, M; Brewster, DH; Going, JJ; Mitchell, DR; Forman, D; McColl, KE
Abstract : Introduction: H.pylori atrophic gastritis and associated hypochlorhydria have been suggested to protect against oesophageal adenocarcinoma (OAD), so that the falling incidence of the former might be linked to the rising incidence of the latter seen recently. If so, a negative association should exist between the incidences of OAD and non-cardia gastric cancer, mediated by atrophic gastritis. Method: In a cross-sectional study, world age-standardised incidences rates (WASR), for the period 2003–07, were abstracted from "Cancer Incidence in Five Continents" Volume X together with 2012 estimates from GLOBOCAN 2012. Relevant ICD-10 codes were used to locate oesophageal and gastric cancers anatomically, and ICD-O3 codes for the histological diagnosis of OAD. In a longitudinal study, trends in WASRs of OAD and total gastric cancer (TGC) were extracted from Cancer in Five Continents Plus (CI5C-Plus). Average annual percentage change (AAPC) in WASRs were calculated for the period 1989–2007 using joinpoint regression. Results: WASRs for the year 2012 were available for 51 countries and showed a negative correlation between OAD and both TGC (men: CC=-0.38, p = 0.006, women: CC=-0.41, p = 0.003) and non-cardia gastric cancer (men: CC=-0.41, p = 0.003 and women: CC=-0.43, p = 0.005). AAPCs were analysed for 38 populations and showed a significant decrease of TGC in 89% and increase of OAD in 66% of the populations, with no population showing a fall in the latter. Significant negative correlations between the incidences of the two cancers were observed in 28 of the 39 populations over the 18–49 years of available observation time. Super-imposition of the longitudinal and cross-sectional data indicated that populations with currently high incidence of OAD and low incidence of gastric cancer had previously resembled countries with high incidence of gastric cancer and low incidence of oesophageal adenocarcinoma. Conclusion: The negative association between OAD and gastric cancer in both recent incidence and over time supports the hypothesis of atrophic gastritis protecting against OAD and also the falling incidence of the gastritis contributing to the rise in the incidence of OAD. Our study also demonstrates the value of the global cancer registry network in identifying disease trends and their implications. Disclosure of interest: None Declared.